The impact and role mechanism of digital finance on the economic development of resource-based cities–an empirical study from China - Qi, Peipei; Wang, Qi (Frontiers in Physics, 2025)
IntroductionIn the new pattern of digital economy, digital finance, as an innovative financial model, is reshaping the development path of cities, yet its impact on resourcebased cities remains largely unexplored.MethodsBased on the panel data of resourcebased cities in China from 2014 to 2023, this paper uses the mediation effect model to investigate the mechanism by which digital finance affects urban economic development through regional innovation and industrial structure. By constructing the urban heterogeneity grouped regression model, this paper analyzes the differentiated impact of digital finance on resource-based cities at different development stages (mature, regenerative, growing and declining). Meanwhile, through the interaction effect analysis, this paper explores the synergistic effect between digital finance and regional entrepreneurship.ResultWe find that (1) Digital finance affects urban economic development through the positive mediating effect of regional innovation and the negative mediating effect of industrial structure, showing significant dual characteristics; (2) Further heterogeneity analysis shows that the impact of digital finance on cities at different stages of development is significantly different: it has the most significant promoting effect on mature and regenerating cities, followed by growing cities, while the effect on declining cities is relatively weak; (3) At the same time, the study identifies the “critical point effect” of digital financial development, which provides a theoretical basis for formulating differentiated urban development strategies.DiscussionThis study systematically reveals the transmission mechanism of digital finance on the economic development of resource-based cities, and provides theoretical basis and practical enlightenment for formulating differentiated digital inclusive financial policies and promoting the high-quality transformation of resource-based cities.